PROBLEMS AFFECTING TO THE PERUVIAN EDUCATIVE SYSTEM - Gómez Gallardo, Luz Marina (2014)
This article aims at spreading information on an unsolved problem of the peruvian educational system. This is depicted by the limited students performance wich is lower than the one stablish by the curriculum. It is clear that resources assigned to basic education are low, and it seems that the State has not assumed, what has to be done to face both problems in an effective way. This gets more complicated due to low quality of metods being used with the students. These matters should be assessed by the State through educational reforms reforms as to obtain positive results in our country, in solving the structural problems of the education. Among them, we highlight: low quality, educational inequity and centralization and increasing the value role being planed by educators. All these is necessary to starts a complete reform (change) of the educational system that will make possible progress and the insertion of our country in a globalised world.